2006
DOI: 10.1002/j.0022-0337.2006.70.8.tb04154.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Dental Public Health Teaching at the Undergraduate Level in Peru

Abstract: There has been a growing interest among dental educators regarding the opportunities offered by community-based dental education as a means to allow dental students to assume their role as health professionals in the real world. Although several dental schools have integrated community-based education into their curricula, most have not engaged their students in the development of competencies to address dental health needs at the community level. The purpose of this article is to discuss the teaching-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Each student is assigned to a community. Full-time dedication provides a more intense and sustained experience than that in the first stage spent in low-income urban communities (6). In these rural and remote areas with few roads, there are minimal supplies of electricity and running water, and only simple radio communication.…”
Section: Dental School Curriculummentioning
confidence: 99%
“…Each student is assigned to a community. Full-time dedication provides a more intense and sustained experience than that in the first stage spent in low-income urban communities (6). In these rural and remote areas with few roads, there are minimal supplies of electricity and running water, and only simple radio communication.…”
Section: Dental School Curriculummentioning
confidence: 99%
“…Outcomes of this scoping review revealed that students benefitted from these university initiatives by having opportunities to work in real-world situations that inspired them to learn [46], practice various procedures, manage the diversity of patients and gain experience working in a team [26]. Indicators for the success of these programs were: students’ satisfaction with the program, community-based experience, enhanced communication skills and self-confidence; a high rate of treated patients; reduced oral health problems in rural areas after rural placements; and an increased percentage of students working in rural dental practices [1, 3, 11, 24–27, 29, 31, 33–43, 47, 4952, 54–65, 67, 68, 7072, 74, 78, 84, 86]. The effectiveness of rural exposure through training in universities and institutions was found to vary due to reasons such as the short duration of rural placement programs, as well as a lack of standardized methodologic and evaluation tools [94].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, quantitative measurements, such as cost per patient, marginal cost and cost analysis [32, 41, 42, 79, 91, 92] were used to measure the cost-effectiveness of various programs. For qualitative measurement, tools, such as data documentation [63], interviews [28, 47, 50, 63, 80] and mixed approaches, questionnaires in combination with focus group discussions, interviews and open-ended questionnaires [34, 38, 48, 59, 67, 71, 72] were used to measure the outcomes.…”
Section: Program Classificationmentioning
confidence: 99%
See 2 more Smart Citations